Highly efficient plasmonic nanofocusing on a metallized fiber tip with internal illumination of the radial vector mode using an acousto-optic coupling approach - Liu Min; Lu Fanfan; Zhang Wending; Huang Ligang; Liang Shuhai; Mao Dong; Gao Feng; Mei Ting; Zhao Jianlin (Nanophotonics, 2019)
Tip-based plasmonic nanofocusing, which delivers light into a nanoscale region and achieves localized electromagnetic (EM) field enhancement beyond the diffraction limit, is highly desired for light-matter interaction-based super-resolution imaging. Here, we present the plasmonic nanofocusing at the apex of a silver (Ag)-coated fiber tip with the internal illumination of a radial vector mode (RVM) generated directly in an optical fiber based on an acoustically-induced fiber grating (AIFG). As illustrated by theoretical calculation, a picture of the nanofocusing plasmonic tip given by analyzing the mode conversion process that the surface plasmon polariton (SPP) mode excited via the radial polarization optical mode can propagate to the apex of the plasmonic tip for nanofocusing because it is not cut off as the tip radius decreases; while the SPP mode which transited from the linear polarization optical mode cannot propagate to the tip apex for nanofocusing because it is cut off as the tip radius decreases. The electric field intensity enhancement factor |Eapex2|/|Einput2|$|{\rm{E}}_{{\rm{apex}}}^{\rm{2}}|/|{\rm{E}}_{{\rm{input}}}^{\rm{2}}|$ of a plasmonic tip with a tip radius of 20 nm was calculated to be ~2 × 103. Furthermore, the electric field enhancement characteristic at the tip apex was also experimentally verified by using surface-enhanced Raman spectroscopy (SERS). The Raman scattering intensity was observed to be ~15 times as strong as that with internal illumination using the linear polarization mode (LPM), revealing their significantly different nanofocusing characteristics. A Raman sensitivity of 10−14m was achieved for the target analyte of malachite green (MG), denoting significant electric field enhancement and effective plasmonic nanofocusing. The energy conversion efficiency of the radial polarization optical mode to the corresponding SPP mode at the tip apex was measured to be ~17%. This light delivery technique can be potentially further exploited in near-field microscopy with improved resolution and conversion efficiency.